Islamophobia in Spain: Inheritance of Reconquista and Hate Political Rhetoric - Farkhani, Farkhani; Baidhawy, Zakiyuddin; Kuswaya, Adang (Journal of Al-Tamaddun, 2021)
The article discusses the development of Islamophobia in Spain and the connection with the ruling of Islam in Andalus, including the impact of Reconquista (re-conquest) that was followed by inquisition; and the connection between Islamophobia and the changing orientalist tradition which impact social and political constellation in Andalus and the West in general up to Post 9/11. Employing a qualitative approach, this study shows that the rise of Islamophobia in Spain in the modern-contemporary era is enabled through the rise of populist politics in Europe in general. Populist rhetoric revives the memories of Islamic domination in Andalus and Reconquista to win votes. Islamophobia is also worsened by Islamophilia— uncritical admiration of the values of Islam, generally associated with an admiration of Islamic civilization and Maurophilia – the explicit romanticization of the Moors in Spanish literature and the complex, often silent presence of Moorish forms in Spanish material culture. This study also demonstrates that hate rhetoric towards Islam in contemporary era is highly influenced by the development of American Orientalism model motivated by war or revenge against terrorism.